Emphasizing the importance of digital storytelling in rural schools in Malaysia - ROZIANA MOHAMED ROSLI (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aimed to examine the degree to which digital storytelling is received favourably or unfavourably by educators and students in rural schools across Malaysia.Method: This study uses a qualitative research strategy known as case studies. Teachers and students are interviewed using the qualitative method. The researchers in this study have also used video recordings of classroom observations to aid in drawing conclusions. Focus Group Discussions (FGD) were held with student groups representing various rural areas in Selangor. Teachers of English at the targeted schools will be interviewed using semi-structured interviews. Finally, video recordings are made of classroom observations in which students do not actively participate.Findings: Results showed that students benefited from participating in storytelling activities. To restate what has already been said, the vast majority of students felt that they had improved in their communication of the target language, their ability to communicate in it, and their self-assurance when doing so.Implications/Novel Contribution: This research investigates what influences students’ communication with and effectiveness at digital storytelling. It also suggests increasing student participation in class discussions to improve education. This study will help us better understand how English language educators and their students view the importance of digital literacy.